English Language Teachers’ Perspectives on Transfer of Training Skills - Bhandari, Bhim Lal (BMC Research Journal, 2025)
Transfer of training is ongoing process of applying the content, instructional knowledge, and skills learned during the training session into classroom practice. This study aimed to explore secondary-level English language teachers' perspectives and the areas in which they get support in the transformation of training skills. The study was conducted using a narrative inquiry method applying semi-structured interviews as tools to get the required information. Four trained English language teachers teaching in four public schools in Rupandehi district were selected purposively. This research revealed that English language teachers had positive perspectives on the transfer of training skills. However, pedagogical transformation through training remained limited as they partially transferred the training knowledge and skills during the classroom delivery. The study can contribute to providing insightful ideas to the teachers in the transformation of training skills.